Influence of Recycled Glass Ceramic Waste on Physical and Mechanical Properties of Foamed Concrete (FC) - Abdul Manaf, Izzati; Marsi, Noraini; Hakim Shariff, Hafizuddin; Kassim, Noraniah (International Journal of Integrated Engineering, 2022)
Glass ceramic waste (GCW) has been left unrecycled due to the challenges it causes. The primary purpose of this research is to find the optimal GCW composition as a quartz sand additive for Foamed Concrete-based Glass Ceramic Waste (FC-GCW) which will reduce the amount of unrecycled GCW that ends up in landfills while producing a sustainable product. The samples were prepared by grinding the GCW and mixing varying percentages of GCW (0, 5, 10, 15, 20, 25, and 30%) with a consistent quantity of cement, quartz sand, water, and foam. Physical and mechanical tests were performed on the samples. During physical tests, the density increased as the GCW percentage increased, but water absorption and porosity decreased. 20% FC-GCW had appropriate density, water absorption, and porosity values of 0.887 g/cm3, 22.6 %, and 88.9%, respectively, which demonstrated that the material is lightweight and porous. For mechanical testing, it was discovered that FC-GCW with 20% GCW addition had the highest average compressive strength of 0.94 MPa and 2.01 MPa for 7 and 28 days, respectively. This research’s contribution can be applied to areas where low densities are preferred and low compressive strength is required, such as replacing existing soil to balance foundations, profiling positive slope to drains of flat concrete roofs, lightweight raft foundation in housing construction, trench reinstatement, soil stabilization by backfill of embankments, floor levelling, blinding concrete for thermal insulation purposes, pipefilling, lightweight foundations, and trench reinstatement.